Statin therapy reduces the likelihood of suboptimal blood pressure control among Ugandan adult diabetic patients - Lumu W; Kampiire L; Akabwai GP; Kiggundu DS; Kibirige D (Dove Medical Press, 2017)
William Lumu,1 Leaticia Kampiire,2 George Patrick Akabwai,3 Daniel Ssekikubo Kiggundu,4 Davis Kibirige5 1Department of Medicine and Diabetes/Endocrine Unit, Mengo Hospital, 2Infectious Disease Research Collaboration, 3Baylor College of Medicine Children’s Foundation, 4Nephrology Unit, Mulago National Referral and Teaching Hospital, 5Department of Medicine, Uganda Martyrs Hospital Lubaga, Kampala, Uganda Background: Hypertension is one of the recognized risk factors of cardiovascular diseases in adult diabetic patients. High prevalence of suboptimal blood pressure (BP) control has been well documented in the majority of studies assessing BP control in diabetic patients in sub-Saharan Africa. In Uganda, there is a dearth of similar studies. This study evaluated the prevalence and correlates of suboptimal BP control in an adult diabetic population in Uganda.Patients and methods: This was a cross-sectional study that enrolled 425 eligible ambulatory adult diabetic patients attending three urban diabetic outpatient clinics over 11 months. Data about their sociodemographic characteristics and clinical history were collected using pre-tested questionnaires. Suboptimal BP control was defined according to the 2015 American Diabetes Association standards of diabetes care guideline as BP levels ≥140/90 mmHg.Results: The mean age of the study participants was 52.2±14.4 years, with the majority being females (283, 66.9%). Suboptimal BP control was documented in 192 (45.3%) study participants and was independently associated with the study site (private hospitals; odds ratio 2.01, 95% confidence interval 1.18–3.43, P=0.01) and use of statin therapy (odds ratio 0.5, 95% confidence interval 0.26–0.96, P=0.037).Conclusion: Suboptimal BP control was highly prevalent in this study population. Strategies to improve optimal BP control, especially in the private hospitals, and the use of statin therapy should be encouraged in adult diabetic patients.Keywords: suboptimal blood pressure control, statin therapy, diabetic, Uganda